(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
This article continues the depth-psychological analysis of the Prayer of the Heart (For the first part, see Louchakova, Existential Analysis, 2007, 18:1, 81-102). Investigations of more than 300 practitioners demonstrate that this core Christian spiritual practice consists of the phenomenological explications of the self, which lead to ego-transcendence and the experience of Union. The ego-transcendence in spiritual experience is contrasted to the other types of ego-transcendence. The mechanisms and the dynamics of ego-transcendence, and the phenomenology of Union are described in detail, emphasizing the dis-identification with the form, paradoxes of the topological shifts of identity and the emergence of gestalt of individual uniqueness in the absence of separateness, dialectics of the devotional I-Though and oneness, and the changes in the intentional consciousness. Analysis of several clinical case studies shows the overall psychological effects of Union, such as actualization of ontopoiesis (intensification of the adult ego-development), and characterological transformation.